If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5 = 3 + 5x Reorder the terms: 5 + 2x = 3 + 5x Solving 5 + 2x = 3 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 5 + 2x + -5x = 3 + 5x + -5x Combine like terms: 2x + -5x = -3x 5 + -3x = 3 + 5x + -5x Combine like terms: 5x + -5x = 0 5 + -3x = 3 + 0 5 + -3x = 3 Add '-5' to each side of the equation. 5 + -5 + -3x = 3 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = 3 + -5 -3x = 3 + -5 Combine like terms: 3 + -5 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667
| 6-5=4x+1 | | 6x+5=4x+1 | | 5805.86=3.14r^2 | | 4j-9j+3=-3 | | (x-7)(y-5)= | | (5x)=(3x+28) | | (3x-1)(3-8x)= | | y=4(7x+100) | | y=1/2+5(0,3) | | (8k-9)(3k-7)= | | 36^1/2 | | x-49=57 | | 9x+6x-12=-7x+2x-12+5 | | -21=y/4 | | 9x-6=3x+6 | | -b=19 | | 6-3x=-5x-2 | | 2x-3x=3-x | | a-16/18=8/9 | | 1/6(5x-9)=7 | | 7-x=6+14 | | 8-4=x+1 | | 6x+4x=10 | | y=x^2*ln(x+2) | | 15x+3y=39 | | 1200=0.18*x | | 1200=0.18x | | -3/4+3/2-2 | | -3x-3x=48-6 | | t^2+7t-18=T+1 | | -19.95-1.10x=-2.35 | | f(x)=3x^3-4x^2 |